2017
DOI: 10.17269/cjph.108.5925
|View full text |Cite
|
Sign up to set email alerts
|

An examination of school- and student-level characteristics associated with the likelihood of students’ meeting the Canadian physical activity guidelines in the COMPASS study

Abstract: OBJECTIVES:To examine school-and student-level correlates of physical activity. METHODS:Cross-sectional Year 2 data collected from 45 298 grade 9-12 students attending 89 secondary schools in the COMPASS study were examined using multi-level modelling to predict the likelihood of students a) achieving 60 minutes of moderate to vigorous physical activity (MVPA) daily; and b) achieving the Canadian Society for Exercise Physiology (CSEP) activity guideline for youth (60 minutes/MVPA daily, vigorous physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 24 publications
(52 reference statements)
2
39
0
2
Order By: Relevance
“…Our findings in relation to PA patterns were consistent with findings in school children and adolescents showing that ethnic minority [ 20 , 29 , 30 ], female sex [ 5 , 8 , 12 14 , 19 21 , 30 , 31 ], higher age [ 8 , 19 ] and indicators of low parental socio-economic status [ 8 , 13 , 14 , 20 ] were negatively associated with PA levels or the likelihood of participating in organised PA. Although a low proportion of students participated in PA at school during leisure time (13%), this finding is encouraging as girls of perceived ethnic minority simultaneously had higher odds of participating in PA at school.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings in relation to PA patterns were consistent with findings in school children and adolescents showing that ethnic minority [ 20 , 29 , 30 ], female sex [ 5 , 8 , 12 14 , 19 21 , 30 , 31 ], higher age [ 8 , 19 ] and indicators of low parental socio-economic status [ 8 , 13 , 14 , 20 ] were negatively associated with PA levels or the likelihood of participating in organised PA. Although a low proportion of students participated in PA at school during leisure time (13%), this finding is encouraging as girls of perceived ethnic minority simultaneously had higher odds of participating in PA at school.…”
Section: Discussionsupporting
confidence: 90%
“…After the separate controlling for factors relating to school leadership, we found an attenuation of the ICC for PA during leisure time, suggesting that at least some of the identified school-level variance is due to facilities or opportunities offered by the schools. In support, secondary schools that offer daily PA and have high quality and accessible PA facilities have been found to be predictive for Canadian students’ time spent on moderate to vigorous PA [ 20 , 21 ]. In this study, perceived ethnic minority, having parents with lower education, higher age and lower school urbanisation degree were independently associated with lower likelihoods of walking or cycling to and from school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using social network analysis, where the full friendship network is modelled, show weak-to-moderate associations between children's self-reported [17][18][19][20][21][22] and objectively-assessed MVPA [23][24][25][26], and there is some evidence indicating potential gender differences [22,26]. At the broader school-level, factors such as support for active transportation, physical activity policies, and facilities, have been shown to be associated with physical activity both in and outside of school time [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence using multi-level modelling consistently shows that children's physical activity levels vary between schools, with the school accounting for between 2% and 10% of the total variance in daily MVPA [27][28][29][30][31][32][33][34][35], indicating that the school environment can influence children's physical activity. Most studies have used self-reported physical activity outcomes, but where objective measures of MVPA have been used, the between-school variance is higher, at around 6%-18% [27,31].…”
Section: Introductionmentioning
confidence: 99%